PERCEPTIONS ABOUT TEACHER’S PROFESSION, FAMILY ENVIRONMENT, SELF-EFFICACY, AND PEERS ON INTEREST TO BECOME TEACHER AMONG FACULTY OF ECONOMICS STUDENTS - Azalia, Farah Cantika; Wolor, Christian Wiradendi; Usman, Osly (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
The purpose of this study was to determine the direct and indirect influence between the perceptions about teacher’s profession, family environment, self-efficacy, and peers on the interest in becoming a teacher in students of the FE UNJ 2019, either partially or simultaneously. This research design is a quantitative approach to the survey method. Data collection technique with a questionnaire using a Likert scale. The data analysis technique was using multiple linear regression using SPSS 24. This study used the "proportionate stratified random sampling" with the slovin formula calculation so that a sample of 162 students was obtained. The results of multiple linear regression are Y = 12.286 + 0.085X1 + 0.153X2 + 0.175X3 + 0.071X4 + 0.806. The results of the F test are F count 21,100 > F table 2.43 and a significance value of 0.000 <0.05. Then the results of the T test on all independent variables have T count > T table 1.97519 and a significance value < 0.05. So based on these calculations, both simultaneously and partially, the variable X1, X2, X3, and X4 have a positive and significant effect on Y. Perceptions about teacher’s profession, family environment, self-efficacy, and peers can explain the bond variable of interest in being a teacher by 35% while the remaining 65% is influenced by other variables outside of this study.